The possibilities of single-port laparoscopic access in cholecystectomy after operations on the abdominal cavity organs - V. M. Klimenko; B. S. Kravchenko; A. O. Steshenko (Zaporožskij Medicinskij Žurnal)
Aim. To assess the possibility and effectiveness of single-port access in cholecystectomy using for chronic calculous cholecystitis in patients who were previously operated on the abdominal organs.